Chepeluk A. D. The ontologic essence of texts of the mixed form (based on German discourse) - Chepeluk A. D. (Philological Treatises, 2020)
This article represents analyses of small texts of German literature, which have characteristics of heterogeneous texts. Attention is paid to the status of the reader in terms of coding and decording matter and to the problems of the translation.